Pterostilbene alleviates liver ischemia/reperfusion injury via PINK1-mediated mitophagy - Qiangqiang Shi; Guangfen Zhao; Susu Wei; Chuanlong Guo; Xianggen Wu; Robert Chunhua Zhao; Guohu Di (Elsevier, 2022)
Hepatic ischemia/reperfusion (I/R) injury contributes to morbidity and mortality during liver resection or transplantation, with limited effective treatments available. Here, we investigated the potential benefits and underlying mechanisms of pterostilbene (Pt), a natural component of blueberries and grapes, in preventing hepatic I/R injury. Male C57BL/6 mice subjected to partial warm hepatic I/R and human hepatocyte cell line L02 cells exposed to anoxia/reoxygenation (A/R) were used as in vivo and in vitro models, respectively. Our findings showed that pretreatment with Pt ameliorated hepatic I/R injury by improving liver histology, decreasing hepatocyte apoptosis, and reducing plasma ALT and AST levels. Likewise, cell apoptosis, mitochondrial membrane dysfunction, and mitochondrial ROS overproduction in L02 cells triggered by the A/R challenge in vitro were reduced due to Pt administration. Mechanistically, Pt treatment efficiently enhanced mitophagy and upregulated PINK1, Parkin, and LC3B expression. Notably, the protective effect of Pt was largely abrogated after cells were transfected with PINK1 siRNA. Moreover, Pt pretreatment promoted hepatocyte proliferation and liver regeneration in the late phase of hepatic I/R. In conclusion, our findings provide evidence that Pt exerts hepatoprotective effects in hepatic I/R injury by upregulating PINK1-mediated mitophagy.